Assessing the Impact of Visual Educational Interventions on User Adoption of Electronic Medical Records in the Inpatient Ward of RSUD Dr. Soeselo, Tegal Regency - Prihati, Eko; Arso, Septo Pawelas; Agushybana, Farid (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Electronic medical records (EMRs) are information systems used to store and manage patients' medical information electronically. Despite being a well-established technology, their implementation often faces resistance, particularly in terms of users' readiness to adapt to new technologies. This study aims to evaluate the acceptance of EMRs among healthcare professionals in the inpatient installation of RSUD Tegal. Methods: The study employed a Quantitative Pre-Experimental method with a One group Pre-test Post-test experimental design. It assessed changes or differences in user acceptance by examining attitudes and behavioral intentions of users before and after learning through video-based instruction. Pre-test and post-test questionnaires were used for data collection. Results: Data analysis revealed an Asymp.Sig. value of 0.000, which is less than 0.05. This indicates that Ho (the null hypothesis) is rejected, suggesting a difference in the average results of the Pre-test on the six variables related to user acceptance of EMRs. Similarly, the Friedman Test Post-test yielded an Asymp. Sig. value of 0.000, also less than 0.05. This further supports the rejection of Ho, indicating a difference in the average results of the six variables. Additionally, the influence of video-based learning on behavioral intentions to use EMRs was determined with a Wilcoxon Signed Ranks Test, resulting in an Asymp.sig (2-tailed) value of 0.000. Conclusion: The study found that there is an increase in behavioral intentions to use EMRs after learning through video-based methods.